DEVELOPMENT DESIGN OF SELECTIVE LISTENING LEARNING MATERIAL BASED ON CORRELATED CORE WITH THE APPLICATION OF LISTENING IN ACTION METHODS - Dedi Zulkarnain Pulungan; Fauziah Nasution; Robiyatul Adawiyah; Elissa Evawani Tambunan; Erni Rawati Sibuea (Universitas Islam Sumatera Utara (UISU), 2019)
The design of the development of learning methods involves the pattern of organizing elements or components in the curriculum. the development of learning materials listening to correlated core-based learning with the application of listening in action methods seen from two dimensions, namely horizontal and vertical dimensions. The horizontal dimension is related to the compilation of the scope of learning content. This spatial arrangement is often integrated with the learning and teaching process. The vertical dimension concerns the compilation of material sequences based on the order of difficulty. Arranged materials start from the easy ones, then go to the more difficult ones, or start with the basic ones followed by the continuation. This development describes in detail about the components that must be present in each listening learning material that can be used for the learning process. The design of the development of the listening learning material consists of several components, including the objectives of the curriculum, teaching materials or the material or content of the curriculum, teaching strategies or teaching methods, teaching media and teaching evaluation and improving teaching. These components are related to each other in the development of learning materials listening to correlated core-based learning by applying listening in action methods.